Students’ Perceptions of Using Yanto Tanjung’s YouTube Channel for Learning TOEFL Reading - Tri Devi Dian Lestari (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explores students’ perceptions of the Yanto Tanjung YouTube channel as a self-learning tool for TOEFL Reading. In recent years, the integration of digital platforms like YouTube into language education has gained increasing relevance, especially as students seek more flexible and engaging methods for mastering specific language skills. This research aims to investigate how learners perceive and utilize the YouTube channel as part of their independent study routines, particularly for improving their TOEFL Reading skills. A qualitative case study approach was employed, involving five undergraduate students from the English Education Department at Universitas Pendidikan Muhammadiyah Sorong. Participants were selected through purposive sampling and interviewed using semi-structured questions. Prior to the interview, students were given approximately three weeks to watch and explore the Yanto Tanjung YouTube channel. Thematic analysis revealed four major themes: perceived usefulness, motivation, autonomous learning, and the perceived effectiveness and limitations of the channel. The findings show that students viewed the channel as highly beneficial in helping them understand TOEFL Reading strategies, with its structured explanations, example-based learning, and approachable teaching style. The channel also played a significant role in enhancing student motivation, fostering engagement, and encouraging note-taking and repetition. Furthermore, students reported that the flexible and on-demand nature of the content supported their autonomous learning, allowing them to review material at their own pace. Despite the overall positive perception, some limitations were noted, such as rapid delivery in certain videos, limited topic coverage, and access restrictions due to paid content. Nevertheless, the study suggests that the Yanto Tanjung YouTube channel serves not only as a supplementary tool but also as a meaningful, adaptive learning strategy in the digital era. It promotes student autonomy, deeper engagement, and can be an effective form of preparation for students planning to take the TOEFL test.